New records of Erythmelus (Hymenoptera: Mymaridae) from the Neotropical region, with description of a new species from Argentina - Triapitsyn, Serguei V. (Zootaxa, 2008)
Several new records of the fairyfly genus Erythmelus Enock (Hymenoptera: Mymaridae) are reported from Argentina, Chile, and Guatemala, since the review by Triapitsyn et al. (2007). Erythmelus (Erythmelus) yuzhanin Triapitsyn sp. n., is described from Córdoba Province, Argentina. A key to the clavatus species group of the nominate subgenus is provided.